ANALISIS TERJEMAHAN TUTURAN YANG MENGAKOMODASI PENYIMPANGAN MAKSIM KUALITAS DALAM NOVEL "ME BEFORE YOU" KARYA JOJO MOYES - Aresta, Ria (PRASASTI: Journal of Linguistics, 2018)
It is not easy to translate the utterances containing flouting maxim quality. The translators should pay more attention in spotting the implied message hidden in it. Therefore, it is important for the translators to consider which translation technique should be applied so that the sense of flouting maxim quality in source text could be deliverd exactly the same in target text. This is descriptive qualitative research with embedded case study. The object of this research is Me Before You novel by Jojo Moyes. In collecting the data, three methods were used; content analysis and focus group discussion (FGD). The data are utterances of all the characters in the plot containing flouting maxim of quality. The assessment of translation quality was obtained from raters and respondents. The results show that the there are 7 strategies used to flouts maxim of quality. They are in form of sarcasm, irony, hyperbole, untrue statement, rhetorical questions, metaphor and simile. The strategy shifts are in the form of (1) sarcasm; sarcasm-statement, sarcasm-sarcasm (downgrading), (2) irony; irony-irony (upgrading), irony-irony (downgrading), (3) hyperbole; hyperbole-hyperbole (downgrading), hyperbole-statement, (4) simile; simile-simile (downgrading), (5) metaphor; metaphor-metaphor (downgrading), while there are no shift in rhetorical question and untrue statement. From the analysis, it is found that 14 translation techniques used by the translator in translating the text, namely, established equivalent, variation, modulation, borrowing (pure borrowing), amplification (explicit), transposition, amplification (addition), reduction, generalization, literal, discursive creation, particularization and description. Established equivalent gives positive effect on translation quality. In the other hand, amplification (addition), discursive creation and literal techniques are known to have negative effect on translation quality.